1,8‐Diazabicyclo[5.4.0]undec‐7‐ene as Cyclic Ether Electrolyte Polymerization Inhibition for Wide‐Temperature‐Range High‐Rate Lithium‐ion Batteries - Hui Tian; Zixin Hong; Zhenhan Fang; Yufeng Luo; Hengcai Wu; Fei Zhao; Qunqing Li; Shoushan Fan; Jiaping Wang (Advanced Science)
Abstract 1,3‐Dioxolane (DOL), with its broad liquid phase temperature window and low Li+‐solvent binding energy, stands out as an ideal solvent candidate for the wide‐temperature and high‐rate electrolytes. Unfortunately, DOL is susceptible to undergo ring‐opening polymerization under common lithium salts, which markedly retards the reaction kinetics. This work introduces the organic basic additive 1,8‐Diazabicyclo[5.4.0]undec‐7‐ene (DBU) to effectively suppress the polymerization, thus achieving compatibility between LiFSI, LiDFOB lithium salts, and DOL. Furthermore, density functional theory (DFT) calculations are utilized to elucidate the underlying mechanisms of DOL polymerization and to clarify how DBU inhibits its polymerization. The resulting electrolyte, devoid of polymer chain formation, forms a weak solvation structure rich in anions, which demonstrates rapid ion transport kinetics in the bulk electrolyte and excellent electrochemical stability at the electrolyte–electrode interfaces (EEIs) simultaneously. When applied to the LiFePO4||graphite full cell, it exhibits exceptional wide‐temperature and high‐rate performance, with specific capacities reaching 101.2 mAh g −1 at room temperature (20 C), 36.9 mAh g−1 at −40 °C (0.5 C), and 118.0 mAh g−1 at 60 °C (20 C). This study significantly guides the development of wide‐temperature, high‐rate electrolytes.